Strokes and Vertebral Artery Trauma - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1994)
Three boys, ages 11, 8, and 7 years, with strokes from vertebral artery lesions resulting from neck trauma are reported from Indiana University School of Medicine, Indianapolis, and Baylor College of Medicine, Houston, TX.